Conceptualizing the self: A critical analysis of the self as a discursive trend in human–computer interaction research - Åhman, Henrik (Human Technology, 2017)
In human–computer interaction (HCI), the human often has been conceptualized as a user. Although this notion has illuminated one aspect of the human–technology relationship, some researchers have argued for the need to explore alternative notions. One such notion becoming increasingly frequent in HCI is the self. In this paper, a study of how the self is described in 88 HCI research publications is presented. Four main aspects of the self are identified: instrumental, communicative, emotional, and playful. These four aspects differ, yet they present the self as stable, coherent, and individual. However, these characteristics have been criticized by several contemporary philosophers. This paper presents arguments from poststructuralist writers as a foundation for advocating the need to develop further these positions within HCI. The theories of Mark C. Taylor, who combines poststructuralism with complexity theory, provide a framework for viewing the self as relational to the extent that interaction becomes an existential process and thus interactive technology constitutes an existential arena.